Game Theory and Wakeup Approach Scheduling in Wireless Sensor Network for Energy Efficiency (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To examine data collection, communication and physical situations, a network with huge sensor nodes called Wireless Sensor Network (WSN) is used. For distributing sensor nodes data, they communicate with base station and it used for storage and remote process. While data transmission, there is a chance for energy problem. In this work, sender is enabled use a reinforcement learning method for predicting receivers’ wake-up times. If sender has a packet for transmission, before receiver’s wake-up time, senders can wake up shortly. This saves the energy used by senders for idle listening. In this condition, trade-off should not be made by senders as its wake-up times are entirely based on wake-up times on receivers. However, trade-off is faced by received. Our proposed technique defines the receiver’s wake-up time for scheduling function and various wake-up intervals are produced due to various parameter selection. In addition, in receiver’s wake-up scheduling function, sender must request parameters before sender making a prediction regarding receiver’s wake-up time.